2008
DOI: 10.1038/sc.2008.151
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord hemangioblastomas in von Hippel–Lindau disease

Abstract: Study Design: Retrospective data analysis. Objective: To clarify the clinical features and surgical management of spinal cord hemangioblastomas in patients with von Hippel-Lindau disease (VHL). Setting: Clinical VHL Research Group in Japan, Japan. Methods: Forty-eight out of 66 patients with associated spinal cord hemangioblastoma among 142 VHL patients were retrospectively examined with respect to clinical features, accompanying lesions and outcome of surgical treatment. Results: Among these 48 patients, 46 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…5,19,24,30 Two studies have analyzed only patients with VHL disease, but the mean follow-up duration did not exceed 4 years. 10,15 In the present study the mean follow-up duration was 7 years and 66% of patients had > 4 years of follow-up. During this period, most patients (85%) remained stable or improved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,19,24,30 Two studies have analyzed only patients with VHL disease, but the mean follow-up duration did not exceed 4 years. 10,15 In the present study the mean follow-up duration was 7 years and 66% of patients had > 4 years of follow-up. During this period, most patients (85%) remained stable or improved.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified tumor volume, anterior location, and the presence of peritumoral edema as predictors of poor surgical outcome. 10,15,25,27 Although we examined all of these factors, only tumor location significantly predicted outcome by multivariate analysis. Functional decline was associated with resection of ventral spinal cord hemangioblastomas, in which decline occurred after 3 of 11 resections for ventrally located tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Additional spinal stenosis, spinal instabilities, spinal deformities, and tumors might cause syrinx formation. 11,12 In an MRI study of 794 asymptomatic adults, PetitLacour et al 13 found a visible central canal in 1.5% of all patients. The diameter ranged between 2 and 4 mm.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to elevated risk for ccRCC, 60%-80% of patients with VHL syndrome, including those with type 2B missense VHL mutations, will develop hemangioblastomas (3)(4)(5). These benign neoplasms are composed of proliferating endothelial and stromal cells that arise in the brain and brain stem, as well as the spinal cord and retina, and often result in catastrophic effects for patients due to their site of presentation (6). Among other functions, the ubiquitin E3 ligase substrate recognition activity of pVHL provides essential modulation of hypoxia-inducible factors (HIFs), which orchestrate transcription of downstream gene targets in proportion to tissue oxygen levels.…”
Section: Introductionmentioning
confidence: 99%